Historical Evolution of Cultural Landscape Studies in Cuba: Trends and Classificatory Perspectives - Alvarez Cruz, Pedro (2024)
This article aims to assess the historical evolution of cultural landscape studies in Cuba and their trends and classificatory perspectives. This study used a documentary research methodology supported by diverse procedures, such as compilation and active reading of documentary sources on the subject in question, internal and external analysis of the information obtained and its synthesis, textual processing, and generalization. This revision facilitated the determination of the main tendencies in the geographical study of Cuba's cultural landscape: 1) cultural landscape as anthropogenic landscape and 2) cultural landscape as heritage. It also presents classificatory perspectives for studying cultural landscape in Cuba based on the analysis of the predominant proposals in the national and international scope.